Le marché anglais : le point de vue d’un courtier d’assurances - Bedford, Peter (Assurances)

(untitled) (HEC Montréal, 1986)
Mr. Peter Bedford participated in a lecture and discussion at the Rendez-Vous de Septembre in Monte Carlo on Tuesday, September 10, 1985. The discussion dealt with the various aspects of the British market. Following we are pleased to present Mr. Bedford's text which gives the point of view of a British broker. As may be noted, the problems he discusses are common to all countries.